Career Development on Employee Performance with Motivation as a Mediating Variable - Chaniago, Dandy; Andriani, Chichi (Human Resource Management Studies, 2024)
This research aims to test (1) the of career development on employee performance, (2) the of career development on employee motivation, (3) the of motivation on employee performance, (4) find out how motivation mediates career development on employee performance The sort of investigate carried out is causative graphic investigate. The populace in this think about were workers of Bank Nagari West Sumatra Head Office with a research test of 157 employees. The sampling technique is cluster proportional random sampling. A questionnaire with a Likert scale as the measurement scale was used to collect data. Data analysis was carried out using SmartPLS 4. The results of this study revealed that (1) there is no direct between career development on employee performance, (2) there is a direct, positive and significant between career development on employee motivation, (3) there is there is a direct, positive and significant between motivation on employee performance on employees, and (4) there is an indirect, positive and significant between career development on employee performance through motivation as a mediating variable on employees.